1999
DOI: 10.1007/s004399900058
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of hereditary multiple exostoses in the Chinese

Abstract: Hereditary multiple exostoses (EXT; MIM 133700) is an autosomal dominant bone disorder. It is genetically heterogeneous with at least three chromosomal loci: EXT1 on 8q24.1, EXT2 on 11p11, and EXT3 on 19p. EXT1 and EXT2, the two genes responsible for EXT1 and EXT2, respectively, have been cloned. Recently, three other members of the EXT gene family, named the EXT-like genes (EXTL: EXTL1, EXTL2, and EXTL3), have been isolated. EXT1, EXT2, and the three EXTLs are homologous with one another. We have identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 11 publications
7
42
1
Order By: Relevance
“…Mutation c.668GϾC (p.R223P), found in one family, is located in the EXT2 region between amino acids 211 and 230, which has been reported to be a MO mutation hot spot. 23,[27][28][29] Two families were diagnosed with deletion 1469delT in exon 6 from EXT1, which was already mentioned to be located in a mutation hot spot by Francannet and colleagues. 25 Finally, missense mutation c.1019GϾT (p.R340L) in EXT1 exon 2 was found in three families and is known to be a recurrent missense mutation in a region that harbors key elements for EXT1 function.…”
Section: Discussionmentioning
confidence: 96%
“…Mutation c.668GϾC (p.R223P), found in one family, is located in the EXT2 region between amino acids 211 and 230, which has been reported to be a MO mutation hot spot. 23,[27][28][29] Two families were diagnosed with deletion 1469delT in exon 6 from EXT1, which was already mentioned to be located in a mutation hot spot by Francannet and colleagues. 25 Finally, missense mutation c.1019GϾT (p.R340L) in EXT1 exon 2 was found in three families and is known to be a recurrent missense mutation in a region that harbors key elements for EXT1 function.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, a similar SSCP analysis in 36 Chinese EXT families suggests the opposite order of importance, with a predominant role for EXT2 (12 families or 33%), while only 5 of these 36 families (14%) showed an EXT1 mutation. No mutation was detected in the 19 remaining families, not even by direct sequencing of the entire coding region of both EXT1 and EXT2 in 13 of these 19 families [Xu et al, 1999]. Finally, a recent study performed on Korean EXT patients showed one EXT1 and one EXT2 mutation in eight families analyzed [Park et al, 1999].…”
Section: Clinical Relevancementioning
confidence: 88%
“…Lack of mutational findings may be due to the limited sensitivity of single strand conformational polymorphism (SSCP) analysis, commonly used in these studies, or to restricted analysis to the EXT1 and EXT2 coding regions and their intron/exon boundaries. Xu et al [1999] examined the EXTL1 and EXTL2 genes for the presence of germline mutations in HME patients, but found no mutations within these genes. This report suggests that mutations in the EXTL family members, if present, are rare compared to mutations in the EXT1 and EXT2 genes.…”
Section: Introductionmentioning
confidence: 98%
“…A small number of reports have demonstrated multiple mutational hits, all of which involve LOH of the EXT1 gene [Bovée et al, 1999;Bernard et al, 2001]. However, most reports fail to identify the predisposing germline EXT1 or EXT2 mutations in 20-50% of reported cases [Raskind et al, 1995;Philippe et al, 1997;Wells et al, 1997;Wuyts et al, 1998;Bovée et al, 1999;Park et al, 1999;Xu et al, 1999;Dobson-Stone et al, 2000;Bernard et al, 2001;Seki et al, 2001]. Lack of mutational findings may be due to the limited sensitivity of single strand conformational polymorphism (SSCP) analysis, commonly used in these studies, or to restricted analysis to the EXT1 and EXT2 coding regions and their intron/exon boundaries.…”
Section: Introductionmentioning
confidence: 98%